Endovideoscopic simple prostatectomy via extraperitoneal research as treatment of benign prostatic hyperplasia - Stanislav N. Volkov; Vitaly I. Tereshchenko; Vladimir S. Stepanchenko; Robert K. Mikheev; Olga R. Grigoryan; Elena N. Andreeva; Konstantim B. Kolontarev (ZAO "Consilium Medicum", 2023)
Aim. To estimate the efficacy of endovideoscopic simple prostatectomy via extraperitoneal research as treatment of benign prostatic hyperplasia. Materials and methods. In the period since January 2021 until May 2022 45 males with prostatic volume 60 g have underwent extraperitoneal endovideoscopic retropubic prostatectomy was. Endovideoscopic research consisted of standard technical steps: the creation of preperitoneal workspace, hemostasis control in the area of lateral peduncles and dorsal venous complex, anterior transverse incision of prostatic capsule, simple prostatectomy and organ extraction. Results. Mean weight of resected prostatic tissue was 79.3±17.4 g. Mean operation time was 104.3±25.4 min. No conversion into open prostatectomy was needed. Blood transfusion was provided in 3 patients. After 6 months 40 patients demonstrated decrease of mean IPSS (International Prostate Symptom Score) from 25.5±2.4 to 6.2±2.1, increase of Qmax from 6.1±2.8 to 18.7±3.4 ml/s. No patients had urinary incontinence. Conclusion. Endovideoscopic retropubic simple prostatectomy via extraperitoneal research (Millin's method) is workable and technically simple surgical method.